EXPERIMENTAL INVESTIGATION ON ELECTRICAL PROPERTIES AND WEAR RATE OF ALUMINUM MATRIX NANOCOMPOSITE (AMNC) OF AA7100/Al2O3 (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In this study AA7100/6wt% Al2O3 metal matrix composite (AMMS) wassuccessfully manufactured using stir casting route. The influence of 6wt% Al2O3content on microstructure, electrical properties and wearresistance were investigated . The microstructure of composite revealed thathomogeneity of Al2O3 particles in the matrix and also the reinforcement ofgrains compared to matrix grains. The homogeneity and reinforcement can beattributed to enhance the electrical and wear properties and this perhaps coulddue to efficiency of stirring process during the casting. The 6wt% Al2O3content shifted the conductivity and permittivity from reducing in matrix toincreasing in the composite when the frequency increased. The wear resistancewas improved due to addition of 6wt% Al2O3 compared to matrix.